(3TQM QSGdI GdOQ GdjJje ddHQchjs - (3eLghds
(3ChdgG (B:s
(3GdMeO ddg Ydi fhGdg hHYO aEf Chdi eG jJhSd Hg Edi fjd GdZaQGf bQGAI cJGH Gddg hcGf ChLR eG Cda aj gPG Gdaf Gdbhje GdQSGdI GdeSeGI HGdOQ GdjJje LeYJ eG jPdd UYGH YHGQGJgG hjSgd WQjb GdhUhd Edi eYGfjgGs
(3BNQgG (B:s
(3ajLH GdJMaX Yf Pdc cdg Gddge GQRbfG GdYUeI Yf GdNWC hGdRdds
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs